Lifestyle and Chronic Pain - Nijs, Jo; Reis, Felipe J J (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cumulating evidence shows that lifestyle factors such as physical (in)activity, stress, poor sleep, unhealthy diet, and smoking are associated with chronic pain severity and sustainment across all age categories. A paradigm shift from a tissue- and disease-based approach towards individually tailored multimodal lifestyle interventions should lead to improved outcomes and decrease the psychological and socioeconomic burden of chronic pain. Such an approach fits well into the global move towards precision pain medicine for patients with chronic pain. For these reasons, this book is dedicated to Lifestyle and Chronic Pain.